Metabolic alterations in patients with essential tremor before and after deep brain stimulation: keys to understanding tremor using magnetic resonance spectroscopy - Göransson, Nathanael; Tapper, Sofie; Lundberg, Peter; Zsigmond, Peter; Tisell, Anders (Frontiers in Neurology, 2025)
IntroductionThe pathophysiology behind essential tremor (ET) and the mechanisms behind the clinical effect after deep brain stimulation (DBS) is not fully understood. This article aims to increase the understanding of ET pathophysiology and the mechanisms behind DBS using magnetic resonance spectroscopy (1H-MRS). Patients with ET underwent MRS scans of the cerebellum and thalamus before and after DBS, and the results were compared to a healthy control group.MethodsTen ET patients and seven healthy controls were included. Preoperatively and 5 months postoperatively, single-voxel MRS was performed on a 1.5 T (tesla) system. Voxels were placed in the thalamus (14 × 13 × 13 mm3), dentate nucleus (13 × 13 × 13 mm3), and cerebellar cortex (13 × 13 × 13 mm3). Metabolite concentrations of total N-acetylaspartate + N-acetyl-aspartyl-glutamate (tNA), total creatine + phosphocreatine (tCr), total choline + phosphocholine + glycerophosphocholine (tCho), and total glutamate and glutamine, which together constitute Glx, were quantified. The patients were evaluated with the Essential Tremor Rating Scale (ETRS) preoperatively and postoperatively.ResultsA total of 14 leads were implanted, and ETRS scores improved significantly following surgery. Thalamic tNA concentrations reduced significantly within the patient group after surgery, as well as in comparison to healthy control values. A significant difference in tNA concentration following surgery was observed only in the thalamus that had been targeted with a lead, not elsewhere. No additional differences in metabolite concentrations (tCr, tCho, Glx) were observed in the thalamic voxel, and none of the studied metabolites (tNA, tCr, tCho, Glx) showed detectable differences in the cerebellar voxels (dentate nucleus and cerebellar cortex).ConclusionIn a highly selected patient group affected by ET, we present novel metabolite information using MRS. Specifically, a reduced thalamic tNA concentration was observed on the lead-implanted side following DBS, suggesting a possible treatment effect.